Plasmonic Properties of Individual Gallium Nanoparticles - Horák, Michal; Čalkovský, Vojtěch; Mach, Jindřich; Křápek, Vlastimil; Šikola, Tomáš (American Chemical Society, 2023)
Gallium is a plasmonic material offering ultraviolet to near-infrared tunability, facile and scalable preparation, and good stability of nanoparticles. In this work, we experimentally demonstrate the link between the shape and size of individual gallium nanoparticles and their optical properties. To this end, we utilize scanning transmission electron microscopy combined with electron energy loss spectroscopy. Lens-shaped gallium nanoparticles with a diameter between 10 and 200 nm were grown directly on a silicon nitride membrane using an effusion cell developed in house that was operated under ultra-high-vacuum conditions. We have experimentally proven that they support localized surface plasmon resonances and their dipole mode can be tuned through their size from the ultraviolet to near-infrared spectral region. The measurements are supported by numerical simulations using realistic particle shapes and sizes. Our results pave the way for future applications of gallium nanoparticles such as hyperspectral absorption of sunlight in energy harvesting or plasmon-enhanced luminescence of ultraviolet emitters.

Gallium is a plasmonic material offering ultraviolet to near-infrared tunability, facile and scalable preparation, and good stability of nanoparticles. In this work, we experimentally demonstrate the link between the shape and size of individual gallium nanoparticles and their optical properties. To this end, we utilize scanning transmission electron microscopy combined with electron energy loss spectroscopy. Lens-shaped gallium nanoparticles with a diameter between 10 and 200 nm were grown directly on a silicon nitride membrane using an effusion cell developed in house that was operated under ultra-high-vacuum conditions. We have experimentally proven that they support localized surface plasmon resonances and their dipole mode can be tuned through their size from the ultraviolet to near-infrared spectral region. The measurements are supported by numerical simulations using realistic particle shapes and sizes. Our results pave the way for future applications of gallium nanoparticles such as hyperspectral absorption of sunlight in energy harvesting or plasmon-enhanced luminescence of ultraviolet emitters.
Plasmonic Properties of Individual Gallium Nanoparticles
Keywords: Electron energy loss spectroscopy; Energy; Gallium; Nanoparticles; Plasmonic nanoparticles; Electron energy loss spectroscopy; Energy; Gallium; Nanoparticles; Plasmonic nanoparticles